2023
DOI: 10.3390/su15118530
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Green Growth Matrix: Exploring the Impact of Green Technology, Climate Change Adaptation, and Macroeconomic Factors on Sustainable Development

Abstract: The primary objective of this paper is to investigate the extent to which climate change adaptation and green technology diffusion serve as key drivers for green growth. Additionally, the study examines the influence of various economic, environmental, and social factors on green growth. Utilizing an annual panel dataset comprising 38 OECD member countries from 1990 to 2020, a series of dynamic panel data models are estimated using the system generalized method of moments (GMM) approach. The empirical results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The escalating utilization of fossil energy sources is mostly responsible for the generation of greenhouse gases (GHGs) and other detrimental gases, which have emerged as a significant worldwide issue (Ali et al, 2022;Borowski, 2022;Raihan, 2023a;Sultana et al, 2023). GHGs have been widely recognized as a pivotal determinant in the phenomenon of global warming, exerting a significant influence on the intricate dynamics of climate change (Agan & Balcilar, 2023;Raihan, 2023b;Voumik et al, 2023). Numerous studies have demonstrated that the utilization of alternative carbon sources such as biomass has the potential to mitigate these difficulties (Sarwer et al, 2022;Raihan, 2023c).…”
Section: Introductionmentioning
confidence: 99%
“…The escalating utilization of fossil energy sources is mostly responsible for the generation of greenhouse gases (GHGs) and other detrimental gases, which have emerged as a significant worldwide issue (Ali et al, 2022;Borowski, 2022;Raihan, 2023a;Sultana et al, 2023). GHGs have been widely recognized as a pivotal determinant in the phenomenon of global warming, exerting a significant influence on the intricate dynamics of climate change (Agan & Balcilar, 2023;Raihan, 2023b;Voumik et al, 2023). Numerous studies have demonstrated that the utilization of alternative carbon sources such as biomass has the potential to mitigate these difficulties (Sarwer et al, 2022;Raihan, 2023c).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by [1], greenhouse gases (GHG), primarily CO 2 , have a significant role to play in aggravating global warming. According to [2][3][4], the consequences of global warming vary across regions globally and are numerous, leading to adverse effects on the health of the population and the environment. Ref.…”
Section: Introductionmentioning
confidence: 99%